Persepsi dan Harapan Masyarakat Lampung terhadap Kitab “Qur’an Terjemahan Bahasa Lampung” dalam Meningkatkan Kearifan Bahasa Lokal - Rohai Inah Indrakasih; Eni Amaliah (UPT Perpustakaan UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Modernization and globalization in the Era 5.0. Only at home, in villages, and in Lampung's minority communities is the Lampung language used for intercommunal communication. English or Indonesian are the two languages most commonly spoken. This survey attempts to give a general picture of how the Lampung population feels about and anticipates the Lampung Language Translation of the Qur'an. The Qur'an's Lampung Language Translation was the subject of a qualitative study to learn how the Lampung people felt about it and what they expected, as well as how to preserve the Lampung language's wisdom and prevent its extinction. The discussion's findings demonstrate that the Lampung translation of the Koran is: 1) Can be found at bookstores, research centers, and libraries; 2) Increase understanding and experience of the contents of the Qur'an; 3) The role of Religious Institutions and Leaders in increasing local language wisdom 4) Recommendations in the form of WEB (Online) applications.